748 HEARING AIDS AND GLASSES: BEDSIDE SIGNS PROMPT ASSESSMENT OF SENSORY NEEDS, AN AUDIT. (8th March 2022) - Laws, E; Currie, H; Batra, R
Abstract: Introduction: It is widely acknowledged that older adults with hearing or visual impairment are at higher risk of developing delirium. The National Institute for Clinical Excellence (NICE) guideline for delirium prevention in the hospital setting emphasises the importance of considering sensory impairment in the clinical assessment of patients at risk of delirium, yet it is often overlooked. This audit aimed to determine doctors' documentation of sensory needs in a geriatrics department and the effect of bedside signs on this documentation. Method: This study analysed documentation for all patients on three elderly care wards. Pre-defined search terms relating to hearing, visual and cognitive impairment were used to analyse whether sensory needs were mentioned during the patients' hospital stay to study date. After the first round of data collection, bedside signs to indicate whether patients have hearing aids or glasses were installed, complemented by ward teaching on sensory impairment and delirium. Documentation was re-audited using the same pre-defined search terms as in the first round. Results: The first round of data collection included 71 patients with an average age of 79 years. Only 30% of patients had documentation regarding sensory needs (hearing and/or vision) and 49% were documented as having delirium and/or dementia. The second round of data collection was completed one month after intervention and included 71 patients with an average age of 82 years. After intervention of bedside signs and ward teaching, doctors' documentation of sensory impairment increased by 81%. Conclusion: Installing bedside signs to indicate whether patients have hearing aids or glasses has improved documentation of sensory impairment, in turn prompting its consideration in assessment and care of patients at risk of delirium.